Characterization of carbon dots covered with polyvinylpyrrolidone and polyethylene glycol - Kudr, Jiří; Richtera, Lukáš; Nejdl, Lukáš; Blažková, Iva; Milosavljević, Vedran; Moravec, Zdeněk; Wawrzak, Dorota; Kopel, Pavel; Ruttkay-Nedecký, Branislav; Adam, Vojtěch; Kizek, René (ESG, 2015)
Luminescent carbon dots are new type of nanomaterial with possible applications in labelling and imaging due to their optoelectronic properties and their superior biocompatibility. The aim of this study was to synthetize two types of C-dots with different polymeric surface modification and to characterize them. Thermal method was used to prepare C-dots with surface stabilization with polyvinylpyrrolidone and polyethylene glycol. Several optical and electrochemical methods were used to characterize the particles. It was found that C-dots-PEG (3 ± 2 nm) possess stronger emission than C-dots-PVP (9 ± 3 nm) within the whole range of excitation wavelengths from 230 to 390 nm. Nevertheless in both cases the portion of C-dots created fluorescent micro-sized particles. Electrochemical impedance spectroscopy revealed that the electrode modified with both types of C-dots significantly increased resistance of bare glassy carbon electrode (C-dots-PVP 34-times and C-dots-PEG 141-times). In addition, it was found that pure polymers and C-dots also exhibit complex concentration dependent behaviour in Brdicka solution measured using hanging mercury drop electrode, whereas low amount added resulted in Co(II) peak (-1.3 V) shift and further resulted in three unresolved peak evolution between -0.5 and -0.9 V.

Luminescent carbon dots are new type of nanomaterial with possible applications in labelling and imaging due to their optoelectronic properties and their superior biocompatibility. The aim of this study was to synthetize two types of C-dots with different polymeric surface modification and to characterize them. Thermal method was used to prepare C-dots with surface stabilization with polyvinylpyrrolidone and polyethylene glycol. Several optical and electrochemical methods were used to characterize the particles. It was found that C-dots-PEG (3 ± 2 nm) possess stronger emission than C-dots-PVP (9 ± 3 nm) within the whole range of excitation wavelengths from 230 to 390 nm. Nevertheless in both cases the portion of C-dots created fluorescent micro-sized particles. Electrochemical impedance spectroscopy revealed that the electrode modified with both types of C-dots significantly increased resistance of bare glassy carbon electrode (C-dots-PVP 34-times and C-dots-PEG 141-times). In addition, it was found that pure polymers and C-dots also exhibit complex concentration dependent behaviour in Brdicka solution measured using hanging mercury drop electrode, whereas low amount added resulted in Co(II) peak (-1.3 V) shift and further resulted in three unresolved peak evolution between -0.5 and -0.9 V.
Characterization of carbon dots covered with polyvinylpyrrolidone and polyethylene glycol
Keywords: Brdicka reaction; carbon dots; nanoparticles; voltammetry; glassy carbon electrode; Brdicka reaction; carbon dots; nanoparticles; voltammetry; glassy carbon electrode